Framing Analysis of Street Race Ancol News on Metro TV - Ramadhan, Tubagus Ryan; Maulianza, Medo (CV. Proaksara Global Transeduka, 2025)
This research is motivated by the inaugural Street Race event initiated by the Metro Jaya Police Chief in early 2022, during which various news programs on Metro TV made several special broadcasts about the Street Race implementation process related to the Metro Jaya Police's efforts to overcome the problem of illegal racing that often occurs in big cities. This research aims to understand why Metro TV is framing the issue of Street Race implemented by Polda Metro Jaya and then associated with Robert N. Entman's framing analysis and how the program constructs it. The literature review in this research includes Mass Communication, Mass Media, Television News, Framing Analysis, Framing Theory According to Robert Entman, and Framing Tools. This research applies a descriptive analysis approach. The descriptive method is used to explore or investigate the events under study. This research describes how framing is formed in news programs, focusing on two dimensions, namely issue selection and emphasis on certain aspects of the issue. The results of the research show the prominence of framing in the reality of the construction of the news of the Inaugural Street Race in Ancol, that the street race event, which was initiated by the Metro Jaya Police Chief, received support and appreciation from various parties, ranging from the Chairman of the Indonesian Motor Association (IMI), Motorsport Observers to the Motorcycle Community. Through the use of this positive framing framework, it succeeded in constructing a narrative that supported police actions in overcoming the illegal races that often happen.